Modern and Contemporary Political Theater from the Levant : A Critical Anthology - Saab, Nada. (Studies on Performing Arts & Literature of the Islamicate World, 2019)
In Modern and Contemporary Political Theater from the Levant, A Critical Anthology , Robert Myers and Nada Saab provide a sense of the variety and complexity of political theater produced in and around the Levant from the 1960s to the present within a context of wider discussions about political theater and the histories and forms of performance from the Islamic and Arab worlds. Five major playwrights are studied, ʿIsam Mahfuz, from Lebanon; Muhammad al-Maghut and Saʿd Allah Wannus, from Syria; Jawad al-Asadi, from Iraq, Syria and Lebanon; and Raʾida Taha, from Palestine. The volume includes translations of their plays The Dictator , The Jester , The Rape , Baghdadi Bath and Where Would I Find Someone Like You, ʿAli? , respectively.